Degradation by water vapor of hydrogenated amorphous silicon oxynitride films grown at low temperature. Issue 1 (December 2017) - Lee, Hyung-Ik; Park, Jong-Bong; Xianyu, Wenxu; Kim, Kihong; Chung, Jae; Kyoung, Yong; Byun, Sunjung; Yang, Woo; Park, Yong; Kim, Seong; Cho, Eunae; Shin, Jai
Abstract We report on the degradation process by water vapor of hydrogenated amorphous silicon oxynitride (SiON:H) films deposited by plasma-enhanced chemical vapor deposition at low temperature. The stability of the films was investigated as a function of the oxygen content and deposition temperature. Degradation by defects such as pinholes was not observed with transmission electron microscopy. However, we observed that SiON:H film degrades by reacting with water vapor through only interstitial paths and nano-defects. To monitor the degradation process, the atomic composition, mass density, and fully oxidized thickness were measured by using high-resolution Rutherford backscattering spectroscopy and X-ray reflectometry. The film rapidly degraded above an oxygen composition of ~27 at%, below a deposition temperature of ~150 °C, and below an mass density of ~2.15 g/cm3 . This trend can be explained by the extents of porosity and percolation channel based on the ring model of the network structure. In the case of a high oxygen composition or low temperature, the SiON:H film becomes more porous because the film consists of network channels of rings with a low energy barrier.